Poly(p-phenylenediamine)/X (X = zinc oxide, cerium oxide, manganese oxide) composites: synthesis, characterization, and electrochemical properties - Huner, Azra (SPRINGER, 2023)
Conductive polymers and transition metal oxides have a wide range of uses and, therefore, intensive research is being done on these systems. In this study, composites of conductive polymer and some transition metal oxides were synthesized and focused on their electrochemical properties. To this end, poly(p-phenylenediamine) (PpPD) and poly(p-phenylenediamine)/X (PpPD/X) composites using zinc oxide (ZnO), cerium oxide ( CeO2), and manganese oxide (MnO) particles as Xs were synthesized by chemical oxidative polymerization. PpPD and PpPD/X composites were characterized by FTIR, UV-Vis spectroscopy, XRD, TGA, and EDX. Their morphology was examined by SEM. For the electrochemical properties of PpPD and PpPD/X composites, cyclic voltammograms and electrochemical impedance spectra were obtained from their solutions in sodium perchlorate/acetonitrile using a triple-electrode system. It was observed that PpPD/X composites were more capacitive than PpPD. The double-layer capacitance (Cdl) given according to the Bode magnitude graph was obtained from the highest PpPD/MnO composite with 0.1 mF, while the lowest was obtained from PpPD with 0.007 mF. Among the PpPD/X composites, the PpPD/MnO composite also showed lower resistance. Cyclic voltammetry and electrochemical impedance spectroscopy results supported each other. After further characterization
Keywords: Metal oxide; Composite; Poly(p-phenylenediamine); Cyclic voltammetry; Electrochemical impedance spectroscopy; P-PHENYLENEDIAMINE; OXIDATIVE COPOLYMERIZATION; O-PHENYLENEDIAMINE; SUPERCAPACITOR; ELECTROSYNTHESIS; POLYMERIZATION; PERFORMANCE; POLYMERS; Polymer Science